Back Cover, Volume 2, Number 2, April 2023. Issue 2 (18th April 2023) - Jiang, Youhua; Machado, Christian; Park, Kyoo‐Chul K.
Abstract : Back Cover : The cover image is based on the Review Article From capture to transport: A review of engineered surfaces for fog collection by Jiang et al. This cover image demonstrates that the collection of fog from an incoming fog‐laden wind includes the aerodynamics‐governed fog‐capturing process and interfacial‐phenomena‐determined liquid transport process. This review introduces and discusses the definition of fog collection, fog capture process, liquid transport process, the effects of surface characteristics on fog collection performance, and the optimization of a fog collector. (DOI: 10.1002/dro2.55 )